Reacting to a Generalised Crisis. A Theoretical Approach to the Consumption of Slack Resources in Family Firms - Agustí, María A.; Ramos, Encarnación; Acedo, Francisco J. (European Journal of Family Business, 2021)
Research to date has shown that companies can accumulate resources over those strictly needed in order to overcome the uncertainty associated to a crisis. But the usage, redeployment, or consumption of this excess of resources when facing an adverse environment is yet underexplored. As suggested by the literature, the condition of family business can exert an important effect in such behaviour. This paper proposes a theoretical framework, focused on family business, about how firms manage the different slack resources when facing a general crisis. We make a call on family business scholars to leverage our propositions and the existing literature on slack resources to develop a guidance for family owners when facing an economic downturn.